2008
DOI: 10.1007/s10856-008-3647-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sintered titanium/hydroxyapatite biocomposite using FTIR spectroscopy

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 43 publications
3
68
0
Order By: Relevance
“…Such peaks are visible in the FTIR spectra for both HA and HA/ZrO 2 coatings (Fig. 4B) and can be attributed to the presence of other calcium phosphate phases, such as tetracalcium phosphate (Ca 4 (PO 4 ) 2 O, TTCP), TCP (Ca 3 (PO 4 ) 2 ) and/or oxyhydroxyapatite (OHA) [34,35]. The structural decomposition of deposited coatings was also revealed by XRD studies (Fig.…”
Section: Characterization Of Deposited Coatingsmentioning
confidence: 81%
“…Such peaks are visible in the FTIR spectra for both HA and HA/ZrO 2 coatings (Fig. 4B) and can be attributed to the presence of other calcium phosphate phases, such as tetracalcium phosphate (Ca 4 (PO 4 ) 2 O, TTCP), TCP (Ca 3 (PO 4 ) 2 ) and/or oxyhydroxyapatite (OHA) [34,35]. The structural decomposition of deposited coatings was also revealed by XRD studies (Fig.…”
Section: Characterization Of Deposited Coatingsmentioning
confidence: 81%
“…The combination of calcium phosphate ceramics and metallic reinforcements has been considered as a promising alternative to achieve both bioactivity and mechanical strength in one material. The most commonly explored combination is the composite containing hydroxyapatite matrix toughened with titanium particles [3][4][5]; however, it has been found that the presence of titanium promotes the partial decomposition of hydroxyapatite during sintering [4]. Therefore, in the present work, we investigated a metal-ceramic composite based on iron and tricalcium phosphate, which could be a good alternative to hydroxyapatite-titanium composites.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different alternatives, titanium and hydroxyapatite are two of the most extensively used materials to treat bone fractures [1,2], so the interactions between them during sintering has been studied in detail [3,4]. The results show that the fabrication of titanium-hydroxyapatite composites is technically feasible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxygen level in sample B was lower than that in sample A, indicating that the oxidation level of sample B was lower than sample A. The presence of Ti in the compound influenced the oxidation level where titanium started oxidising at a low temperature of 450°С compared to HA which started to decompose at above the temperature of 850°С [40]. It is clear that the oxidation level of sample A was higher than sample B due to the high proportion of Ti in the sample.…”
Section: Energy-dispersive X-ray Spectroscopymentioning
confidence: 96%